Treatment of the Fixation Surface Improves Glenoid Prosthesis Longevity in vitro. - Junaid,S; Sanghavi,S; Anglin,C; Bull,A; Emery,R; Amis,AA; Hansen,U (Journal of Biomechanics, 2017)
Many commercial cemented glenoid components claim superior fixation designs and increased survivability. However, both research and clinical studies have shown conflicting results and it is unclear whether these design variations do improve loosening rates. Part of the difficulty in investigating fixation failure is the inability to directly observe the fixation interface, a problem addressed in this study by using a novel experimental set-up. Cyclic loading-displacement tests were carried out on 60 custom-made glenoid prostheses implanted into a bone substitute. Design parameters investigated included treatment of the fixation surface of the component resulting in different levels of back-surface roughness, flat-back versus curved-back, keel versus peg and more versus less conforming implants. Visually-observed failure and ASTM-recommended rim-displacements were recorded throughout testing to investigate fixation failure and if rim displacement is an appropriate measure of loosening. Roughening the implant back (Ra>3µm) improved resistance to failure (P<0.005) by an order of magnitude with the rough and smooth groups failing at 8712±5584 cycles (mean±SD) and 1080±1197 cycles, respectively. All other design parameters had no statistically significant effect on the number of cycles to failure. All implants failed inferiorly and 95% (57/60) at the implant/cement interface. Rim-displacement correlated with visually observed failure. The most important effect was that of roughening the implant, which strengthened the polyethylene-cement interface. Rim-displacement can be used as an indicator of fixation failure, but the sensitivity was insufficient to capture subtle effects. LEVEL OF EVIDENCE: Basic Science Study, Biomechanical Analysis.